The Role of a Simulation-Based Activity on Student Perceptions of Parenteral Nutrition Education - Genene Salman; Henry Hua; Michelle Nguyen; Sandy Rios; Elvin A. Hernandez (MDPI AG, 2020)
Introduction: Parenteral nutrition (PN) education in pharmacy schools and postgraduate programs may not sufficiently prepare future pharmacists for clinical practice. Limited data exist regarding innovative teaching strategies in the area of PN. The purpose of this study was to identify students' perceptions of a simulated PN activity in a pharmacotherapeutics course. Methods: Second-year Doctor of Pharmacy (PharmD) students from two cohorts (N = 84 for both cohorts) completed a PN assignment using simulated PN materials, which resembled those seen in clinical practice. Before and after the activity, students completed identical surveys about their perceived competence and interest in PN, which were analyzed using Wilcoxon signed-rank tests. Results: Following the simulation, the percentage of students affirming their perceived competence (selecting strongly agree or agree in the survey) in their ability to describe the process of combining ingredients to make a PN admixture (45.2% vs. 83.3%, p < 0.001) and calculate PN-related problems (58.3% vs. 83.3%, p < 0.001) improved. The proportion of students expressing interest in PN increased after the simulation (78.6% vs. 86.9%, p < 0.001). Conclusion: A simulated practicum experience in PN was viewed positively by PharmD students at this university, and may be a valuable active learning experience to incorporate in a PharmD curriculum.